Educational Play Tools (APE) to Provide Understanding of the Dangers of Excess Sugar Consumption in Early Childhood - Rendy Setyowahyudi; Ni Putu Vivin Indrawati; Sumiati; Made Vina Arie Paramita (Universitas Pendidikan Ganesha, 2026)
Kidney failure cases requiring dialysis at an early age are common, and the number of cases continues to rise. One of the main causes is excessive sugar consumption from an early age. The purpose of this activity is to increase the knowledge of parents and kindergarten teachers in Cluster V, Buleleng District, regarding the dangers of excessive sugar consumption, as well as to improve the skills of kindergarten teachers in Cluster V, Buleleng District, in creating and using learning media in the form of educational games that can be used to educate and prevent excessive sugar consumption in early childhood. This community service activity was carried out in five stages: socialization, training, technology implementation, mentoring, and program sustainability. The activity was carried out by targeting kindergarten teachers in Cluster V, Buleleng District, which consists of six schools. Evaluation was carried out through four methods: tests, interviews, observation, and documentation. The results obtained from the tests, interviews, and documentation showed understanding and the ability to create educational games during the training. The results of observations conducted during the mentoring showed that teachers were able to apply educational games to students in their institutions to educate children about the dangers of excessive sugar consumption. This community service activity concludes that there is an increase in the knowledge and skills of kindergarten teachers in Buleleng District V in making and using Educational Play Tools to educate early childhood about the dangers of excessive sugar consumption.